Evaluation of a New 3‐Dimensional Color Doppler Flow Method to Quantify Flow Across the Mitral Valve and in the Left Ventricular Outflow Tract: An In Vitro Study. (1st February 2014) - Kimura, Sumito; Streiff, Cole; Zhu, Meihua; Shimada, Eriko; Datta, Saurabh; Ashraf, Muhammad; Sahn, David J.
Abstract : Objectives: The aim of this study was to assess the accuracy, feasibility, and reproducibility of determining stroke volume from a novel 3‐dimensional (3D) color Doppler flow quantification method for mitral valve (MV) inflow and left ventricular outflow tract (LVOT) outflow at different stroke volumes when compared with the actual flow rate in a pumped porcine cardiac model. Methods: Thirteen freshly harvested pig hearts were studied in a water tank. We inserted a latex balloon into each left ventricle from the MV annulus to the LVOT, which were passively pumped at different stroke volumes (30–80 mL) using a calibrated piston pump at increments of 10 mL. Four‐dimensional flow volumes were obtained without electrocardiographic gating. The digital imaging data were analyzed offline using prototype software. Two hemispheric flow‐sampling planes for color Doppler velocity measurements were placed at the MV annulus and LVOT. The software computed the flow volumes at the MV annulus and LVOT within the user‐defined volume and cardiac cycle. Results: This novel 3D Doppler flow quantification method detected incremental increases in MV inflow and LVOT outflow in close agreement with pumped stroke volumes (MV inflow, r = 0.96; LVOT outflow, r = 0.96; P < .01). Bland‐Altman analysis demonstrated overestimation of both (MV inflow, 5.42 mL; LVOT outflow, 4.46 mL) with 95% of points within 95% limits of agreement. Interobserver variability values showed good agreement for all stroke volumes at both the MV annulus and LVOT. Conclusions: This study has shown that the 3D color Doppler flow quantification method we used is able to compute stroke volumes accurately at the MV annulus and LVOT in the same cardiac cycle without electrocardiographic gating. This method may be valuable for assessment of cardiac output in clinical studies.